2021
DOI: 10.1002/jclp.23119
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depression in psychotherapy: How client characteristics predict clinical improvement

Abstract: Objective: The current study aims to ascertain the trajectories of psychotherapy clients' symptom change and identify client factors that predict treatment outcome. Method:We conducted a latent growth mixture model (LGMM) to identify the change trajectories of 44 clients' depression scores during psychotherapy. Client characteristics were then explored to determine whether any were associated with change trajectories. We examined whether the number of physician visits and/or client selfconcealment scores predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…However, the result should be interpreted with caution. Other studies have found superior fit with different classes (see Lin & Farber, 2021; Palmer et al, 2021 [two classes] and Ellis et al, 2017 [four classes]) and it is possible that a model with four or more classes would be a better fit had the models terminated normally. Lastly, see Table 4 for the Reliable Change Index (RCI) for the full sample and the three latent classes…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the result should be interpreted with caution. Other studies have found superior fit with different classes (see Lin & Farber, 2021; Palmer et al, 2021 [two classes] and Ellis et al, 2017 [four classes]) and it is possible that a model with four or more classes would be a better fit had the models terminated normally. Lastly, see Table 4 for the Reliable Change Index (RCI) for the full sample and the three latent classes…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have further utilized treatment trajectory studies to understand the symptom changes for patients suffering from specific diagnostic issues, such as depression. Most recently, Lin and Farber (2021) conducted a LGMM to identify change trajectories for individuals suffering from depression and receiving outpatient psychotherapy. Results indicated two trajectories—those whose depression symptoms improved and those who did not.…”
mentioning
confidence: 99%
“…While these findings consistently demonstrate that session frequency is associated with treatment outcome based on the average level of change for the entire sample, it should not be assumed that all clients respond to psychotherapy of a certain frequency in a similar manner. Since clients fall into heterogeneous trajectories of change even when receiving the same treatment (Lin & Farber, 2021; Owen et al, 2015; Palmer et al, 2021), the average outcome may fail to capture individual differences in treatment responses. Although weekly therapy results in a faster improvement trajectory than biweekly therapy on average (Erekson et al, 2015), the average trajectories may not apply to each individual.…”
Section: Session Frequencymentioning
confidence: 99%
“…The treatment outcome package (TOP) used by Nordberg et al, the same instrument as used by Jankowski et al (2019), was also used in this study. Last, Lin and Farber (2021) used the TOP depression subscale to model change trajectories, using a sample of outpatient clients, some of whom received psychodynamic treatment. They found two subgroups: a moderate symptom subgroup of improvers and a high symptom subgroup of non-improvers.…”
Section: Introductionmentioning
confidence: 99%